ECONOMICAL PERFORMANCE OF STOCK EXCHANGE LISTED HOTELS IN INDIA - Sharma, Jitin; Khurana, Gaurav (International Journal of Psychosocial Rehabilitation, 2020)
This research study focuses on the overall performance of hotels that are listed on the Indian stock exchange over the last two years. Contributions from the HR office, general administration, and senior administration of five-star lodgings across India were analysed qualitatively. As a result, it enhances information about the influence of the COVID-19 situation on the friendliness business’ (HR), technique, and business activities. The review inspects subjective information accumulated from 17 high level supervisors of five-star inns across India by means of online meetings. The substance has been examined, and the main revelations with useful importance have been stressed. This initial examination concerning the Indian lodging business uncovers how hoteliers are presently managing the pandemic the nation over.